Comparative Analysis of the Effect of the Evolution of Energy Saving Regulations on the Indoor Summer Comfort of Five Homes on the Coast of the Basque Country - Jorge Otaegi; Rufino J. Hernández; Xabat Oregi; Alexander Martín-Garín; Iñigo Rodríguez-Vidal (Buildings, 2022)
In the last decade, several European directives have been established to contribute to the 2020, 2030 and 2050 energy saving targets and impose energy efficiency requirements for new construction, existing buildings and building renovation operations. One of the ways to achieve said objectives is to rely on the most demanding energy efficiency labels existing in Europe, such as Passivhaus, and to implement similar concepts into the national energy regulations of European countries based on a high-performance thermal envelope (high insulation and high-performance windows), high airtightness and high-performance heat-recovery ventilation systems, and solar heat harvesting. This energy conservation concept has shown to be effective for houses with low-density occupation in cold climates, but may cause severe overheating problems in denser collective housing in temperate and hot climates with higher solar radiation. To assess this impact, five flats in three developments from different periods that range from no insulation at all to a nZEB, Passivhaus-certified high-rise are compared in this paper, using data from a monitoring campaign during the summer of 2020. The results show and quantify the strong impact the evolution of the energy saving regulatory trend has had on summer indoor comfort, which may in some cases lead to previously unnecessary air conditioning for cooling and, ultimately, be counterproductive towards the end goals of reducing energy consumption and greenhouse-effect gas emissions and mitigating climate change.